2009
DOI: 10.3928/01477447-20090501-01
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 78 Patients With Spinal Injuries in the 2008 Sichuan, China, Earthquake

Abstract: To analyze the clinical features of patients with spinal injuries and to better cope with future disasters, we retrospectively reviewed 78 patients' medical records after the 2008 Sichuan, China, earthquake. All patients survived, and the mean time patients spent under rubble was 12.2 hours. The largest number of victims were in the 30- to 39-year age group (24.3%), followed by the 20- to 29-year age group (21.8%) and the 40- to 49-year age group (20.5%). Isolated spinal injuries occurred in 55 patients (71.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
2
13
1
Order By: Relevance
“…This finding is similar to that of the studies on the neurosurgical complications during the previous earthquakes 310 11 12 In studies performed after the Sichuan, China earthquake in 2008, 40-55% of the patients with spinal injuries were reported to suffer from lumbar involvement 1011 12 Interestingly, in a similar report after Yushu, China earthquake in 2010, Li and colleagues detected lumbar fracture in almost 70% of the patients with spinal fractures 3.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is similar to that of the studies on the neurosurgical complications during the previous earthquakes 310 11 12 In studies performed after the Sichuan, China earthquake in 2008, 40-55% of the patients with spinal injuries were reported to suffer from lumbar involvement 1011 12 Interestingly, in a similar report after Yushu, China earthquake in 2010, Li and colleagues detected lumbar fracture in almost 70% of the patients with spinal fractures 3.…”
Section: Discussionsupporting
confidence: 83%
“…The most important factors predicting the extent of recovery are the primary neurological state, location of injury within the spinal cord, trauma mechanism, vertebral fracture type and location, and patient age [34567]. …”
Section: Discussionmentioning
confidence: 99%
“…The chances of neurological recovery and improvement are different in different patients and depend on various factors, including primary neurological state, trauma mechanism, vertebral fracture type and location, and age. Complete SCI, older age, thoracic fractures, and fractures accompanied by dislocations generally follow a more dismal prognosis [34567]. Among all these factors, the extent of neurological deficits (mostly based on the American Spinal Injury Association [ASIA] classification [8]) has been considered the most important predictive factor for functional outcome and prognosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Seven of these papers were excluded either due to lack of epidemiological data on SCI 6,7 or because they cited earlier publications. [8][9][10][11][12] The remaining eight studies [13][14][15][16][17][18][19][20] were analyzed. Three additional papers on SCI following the EQs in China and Haiti [21][22][23] written by the authors (JR, JG) and another paper by Burns 24 were identified by manual search.…”
Section: Methodsmentioning
confidence: 99%
“…Study parameters, population demographics, SCI characteristics (level of lesion and neurological deficit), medical complications and deaths due to complications are presented. Some studies 13,14,17,18 were not SCI-specific and therefore do not provide information on this population. Even some SCIspecific studies 15,24 provide only limited data on SCI characteristics and complications.…”
Section: Selected Data From Recent Severe Eqsmentioning
confidence: 99%